2015
DOI: 10.1002/lom3.10071
|View full text |Cite
|
Sign up to set email alerts
|

A new robust oxygen‐temperature sensor for aquatic eddy covariance measurements

Abstract: The fragility of thin Clark‐type glass microelectrodes used in aquatic eddy covariance measurements of benthic oxygen fluxes is a challenge when using this powerful technique. This study presents a new fast‐responding dual oxygen‐temperature sensor for eddy covariance measurements that is far more robust. Response time tests in the lab, where the sensor was inserted from air into water, revealed 90% response times of 0.51 s and 0.34 s for oxygen and temperature measurements, respectively. In wave tank tests, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 51 publications
3
68
0
Order By: Relevance
“…The somewhat slower response found in the field, where the sensor was permanently under water, was likely caused by oxygen concentration equilibration through the 6730 P. Berg et al: Technical Note: Time lag correction of aquatic eddy covariance data thin boundary layer flow that forms over the oxygen sensing foil . Through detailed model calculations, Berg et al (2015) showed that a sensor with this response time will virtually capture the entire flux signal if a time lag correction is applied. Specifically, the underestimation of the flux was found to be less than 5 %, even in challenging situations at shallow-water sites with substantial unidirectional current flow, where small rapid eddies dominated the vertical turbulent mixing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The somewhat slower response found in the field, where the sensor was permanently under water, was likely caused by oxygen concentration equilibration through the 6730 P. Berg et al: Technical Note: Time lag correction of aquatic eddy covariance data thin boundary layer flow that forms over the oxygen sensing foil . Through detailed model calculations, Berg et al (2015) showed that a sensor with this response time will virtually capture the entire flux signal if a time lag correction is applied. Specifically, the underestimation of the flux was found to be less than 5 %, even in challenging situations at shallow-water sites with substantial unidirectional current flow, where small rapid eddies dominated the vertical turbulent mixing.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Berg et al (2015) showed through modeling that when, for example, a 0.5 Hz sinusoidal wave signal in oxygen concentration is measured with a sensor with a response time (t 90% ) of 0.5 s, a 0.20 s phase shift, or time lag, is introduced in the recorded data. While this inevitably will add substantial time lag bias to calculated fluxes unless a time lag correction is applied (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From these fluxes, we derived exchange coefficients for O 2 , and then standard gas exchange coefficients (k 600 ). All measurements were done from a floating platform, and because we used a newly developed fast-responding dual O 2 -temperature sensor (Berg et al, 2016), we were able to derive parallel fluxes of O 2 and thermal energy, or sensible heat. We conducted proof-of-concept tests that were up to 40 h long at three river sites.…”
Section: Scope Of Workmentioning
confidence: 99%
“…The O 2 concentration was measured with a new fastresponding dual O 2 -temperature sensor (RINKO EC, JFE Advantech, Japan) developed specifically for eddy covariance measurements (Berg et al, 2016). This sensor allows for deriving simultaneous fluxes of O 2 and heat.…”
Section: Floating Measurements Platformmentioning
confidence: 99%